(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Osimertinib is a newly approved treatment line for the non-small cell lung carcinoma actively caused by mutation in EGFR and T790M. The present study was targeted to originate a validated method for the qualification as well as quantification of osimertinib through RP-HPLC in bulk and its pharmaceutical formulation. The mobile phase, 65% triethylamine buffer (pH 2.5) and 35% acetonitrile (v/v) was run through a prontosil column (C18, 4.6×150 mm i.d., 3.5 μm particle size) at a flow rate of 0.7 ml/min. A PDA plus detector was used to scan the absorbance over 210 to 360 nm. Validation study performed following the ICH guidelines Q2 (R1) was found the developed method to be specific, precise, accurate, linear over the range of 64–96 μg/ml with R2 > 0.999, robust and rugged. The % recovery of osimertinib at different levels ranged between 99.32% and 100.37% from tablet formulation (Osicent). The method holds promise for analysis of osimertinib in bulk, pharmaceutical formulations and for further research. Bangladesh Pharmaceutical Journal 27(1): 85-91, 2024 (January)